Total Hip and Knee Replacements 2011: An Update for Rheumatologists - Gordon, Debra (MD Conference Express, 2011)
An aging population, obesity, and the growing incidence of knee injuries in young people are factors that are likely to increase the demand for total joint replacement. This article discusses physical activity and osteoarthritis, as well as outcomes of total hip and total knee replacements.